Studying and forecasting of the phosphates pollution dynamics in watersheds and antropogenic water management landscape dynamics: application to the small carpathians rivers’ watersheds - Glushkov, Alexander; Khokhlov, Valery; Serbov, Mykola; Buyadzhi, Vasily; Bunyakova, Yuliya; Solyanikova, Elena (Publishing House of Lviv Polytechnic National University, 2016)
The paper concerns the results of the quantitative study of dynamics for phosphates concentrations in the Small Carpathians rivers watersheds in Earthen Slovakia by using methods of nonlinear analysis and forecasting, chaos theory and dynamical systems. The conclusions can be viewed from the perspective of carrying out new algorithms for analysis and forecasting of the dynamics and evolution of anthropogenic water management landscape. Chaotic behaviour of the phosphates concentration time series in the watersheds of the Small Carpathians is studied. It is shown that low-D chaos exists in the time series under investigation.
Keywords: dynamics; studying; forecasting; phosphates concentrations; the Small Carpathians rivers watersheds; chaos theorymethods